Comparative Analysis of Embryological Stages in the Qur'an and Contemporary Science - Ahmad Soib; Dwi Purbaningrum (al-Afkar, Journal For Islamic Studies, 2026)
This article analyzes the correspondence between the embryological stages described in the Qur'an and contemporary scientific findings through a comparative and analytical approach. The study focuses on the description of the stages of human creation in Surah Al-Mu'minun: 12–14, which includes the stages of nuthfah, 'alaqah, mudghah, and bone formation and flesh formation. This Qur'anic description is then examined by comparing it to the scientific classification of the processes of fertilization, implantation, somite formation, and organogenesis as described in modern embryology. This study attempts to demonstrate that although the Qur'an was not intended as a biological text, its step-by-step narrative has relevant conceptual correspondences with scientific findings, particularly in describing the gradual transformation of embryonic growth. Furthermore, this study emphasizes that the dialogue between interpretation and science should not be directed at forcing literal similarities, but rather at finding epistemological common ground that can enrich understanding of the Qur'an's message and contribute to the development of scientific interpretation studies. The results of the study show that a proportional comparative approach can open up space for constructive integration between the text of revelation and modern science.